Meteorological driving mechanisms and human impacts of the February 1979: extreme hydro-geomorphological event in Western Iberia - Rebelo, Luís (2018)
The large number of floods and landslides that occurred on 5–16 February 1979 in Portugal was a major hydro-geomorphologic extreme event according to the DISASTER database in terms of number of displaced people. The February 1979 event is the top ranked episode in terms of the total number of evacuated people (4244), displaced people (14,322) and also on the number of days of event duration (12 days) for the period 1865–2015. In this event, 62 damaging floods and five damaging landslides causing eight fatalities were recorded in Portugal. This event was driven by an unusually intense atmospheric forcing mechanism acting at different time scales. Despite the intense magnitude and the widespread impact on the population, this event has not been studied in detail. In this study, we show that the precipitation period of February 1979 had produced several multi-day accumulated precipitation events over the Portuguese continental territory, ranking among the top 10 events observed between 1950–2008. Additionally, most of the precipitation from this event occured in days in which atmospheric circulation was dominated by “wet” circulation weather types (CWTs), namely, cyclonic (C), west (W) or southwest (SW) types.